2023
DOI: 10.3389/fpls.2023.1082094
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of tomato WAT1 leads to reduced susceptibility to Clavibacter michiganensis through downregulation of bacterial virulence factors

Abstract: Tomato bacterial canker caused by Clavibacter michiganensis (Cm) is considered to be one of the most destructive bacterial diseases of tomato. To date, no resistance to the pathogen has been identified. While several molecular studies have identified (Cm) bacterial factors involved in disease development, the plant genes and mechanisms associated with susceptibility of tomato to the bacterium remain largely unknown. Here, we show for the first time that tomato gene SlWAT1 is a susceptibility gene to Cm. We ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…All GA, JA, and ET were likely to be elevated upon Cn due to increased expression of multiple genes involved in their biosynthesis, including genes encoding ent-copalyl diphosphate synthase, ent-ekaurene oxidase (KO), and GA 2-oxidase for GA biosynthesis ( Sakamoto et al 2004 ); genes encoding allene oxide synthase and genes encoding lipoxygenases for JA biosynthesis ( Wasternack and Hause 2013 ); and genes encoding the 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase and the ACC synthase family genes for ET biosynthesis ( Wang et al 2002 ). Consistently, a recent study also indicated the plant host manipulated the levels of auxin and ET to combat the clavibacter infection ( Koseoglou et al 2023 ). Fewer genes involved in brassinosteroid, cytokinin, and SA were induced by Cn ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…All GA, JA, and ET were likely to be elevated upon Cn due to increased expression of multiple genes involved in their biosynthesis, including genes encoding ent-copalyl diphosphate synthase, ent-ekaurene oxidase (KO), and GA 2-oxidase for GA biosynthesis ( Sakamoto et al 2004 ); genes encoding allene oxide synthase and genes encoding lipoxygenases for JA biosynthesis ( Wasternack and Hause 2013 ); and genes encoding the 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase and the ACC synthase family genes for ET biosynthesis ( Wang et al 2002 ). Consistently, a recent study also indicated the plant host manipulated the levels of auxin and ET to combat the clavibacter infection ( Koseoglou et al 2023 ). Fewer genes involved in brassinosteroid, cytokinin, and SA were induced by Cn ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, Walls Are Thin1 ( WAT1 ) in tomato was shown to be a susceptibility gene to Cm. Inactivation of WAT1 enhanced tomato resistance to diverse Cm strains, likely through reducing auxin and ethylene (ET) content in plants, as well as suppressing the production of virulence factors in bacteria ( Koseoglou et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%